2018
DOI: 10.1038/s41598-018-33027-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatic alterations in circulating cell-free DNA of oesophageal carcinoma patients during primary staging are indicative for post-surgical tumour recurrence

Abstract: Oesophageal cancer (OC) has high mortality. This study aims at determining the feasibility of liquid biopsies for genomic profiling in early stage OC, comparing two different technologies for mutational analysis in circulating cell -free DNA (ccfDNA) and evaluating the clinical impact of these somatic alterations during primary staging. In 25 patients with locally advanced OC, endoscopic tumour biopsies and simultaneous blood samples were taken during primary staging. Genomic DNA from biopsies and ccfDNA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…It also took a precondition that objective mutation sites must be certainly known in advance. In other words, NGS is more suitable for primary gene profiling on multi-gene panels [22].…”
Section: Storage and Detection Methods For Cfdnamentioning
confidence: 99%
See 1 more Smart Citation
“…It also took a precondition that objective mutation sites must be certainly known in advance. In other words, NGS is more suitable for primary gene profiling on multi-gene panels [22].…”
Section: Storage and Detection Methods For Cfdnamentioning
confidence: 99%
“…The increase of cfDNA level and copy number in tumor patients are explained by the raised number of apoptotic and necrotic carcinoma cells. It has been proven in liver cancer, oesophageal cancer, breast cancer, and pancreatic cancer [22,52,53]. Recently, Yan L et al clearly showed that the cfDNA concentration in plasma was significantly higher in HCC patients compared to patients with liver fibrosis or healthy individuals [25].…”
Section: Cfdna Quantitative Determinationmentioning
confidence: 99%
“…ddPCR detects mutations in cfDNA with high sensitivity, but it is only suitable when the mutations are already known from previous tumor tissue‐based analyses [42]. Also, the location of somatic mutations in EC‐related driver genes span large regions of the genome [43], which are difficult to track by PCR‐based methods.…”
Section: Cfdna Detection and Analysismentioning
confidence: 99%
“…Clinically relevant biomarkers are genetic, epigenetic, proteinic, or cellular alterations that are intrinsic to cancer cells. These biomarkers can be used to predict patients' responses to Huang et al [50] , 2017 Pasternack et al [112] , 2018 Kakiuchi et al [42] , 2014 Yoshida et al [113] , 2019 Nagahashi et al [39] , 2016…”
Section: Biomarkers For Gi Cancermentioning
confidence: 99%
“…TP53 was commonly implicated in all references except 28035762, 30297788 and 30523343 (PMID) [50,112,117] . EC: Esophageal cancer; GC: Gastric cancer; CRC: Colorectal cancer; NGS: Next-generation sequencing; FFPE: Formalin-fixed paraffin-embedded; N/A: Not available; EBV: Epstein-Barr virus; MSI: Microsatellite instability; NGS: Next-generation sequencing.…”
Section: Fbxw7 Braf Smad4 Met Fgfr1mentioning
confidence: 99%